Rights of an accused - Verma, R. S.; Thokchom, I. B. S. (Delhi : Verma Publications, 1999)
Reports of cases decided by Supreme Court of India and all High Courts relating to rights of an accused; also includes extracts of various acts and constitution of India as amended upto date.
Includes bibliographical references and index.
eng.
Keywords: Criminal procedure -- India -- Digests; Fair trial -- India -- Digests; Civil rights -- India -- Digests